Stakeholder influences on sustainability practices in the Canadian forest products industry - Sharma, Sanjay; Henriques, Irene (Strategic Management Journal, 2004)
Abstract We examined how managers' perceptions of different types of stakeholder influences in the Canadian forestry industry affect the types of sustainability practices that their firms adopt. Both influences involving withholding of resources by social and ecological stakeholders and those involving directed usage of resources from economic stakeholders were found to drive such practices. We found that the industry and its stakeholders have moved beyond a focus on early stages of sustainability performance such as pollution control and eco‐efficiency. However, more advanced practices, such as those involving the redefinition of business and industrial ecosystems where firms locate in a region so that they can exchange and utilize wastes generated by other firms, are in their infancy. Stakeholders and firms in the industry are focused on the intermediate sustainability phases involving recirculation of materials and redesign of processes including sustainable harvesting of lumber. Copyright © 2004 John Wiley & Sons, Ltd.